THE MARKOV MODEL OF QUANTIUM STATE SYSTEM EVOLUTION IN TERMS OF MACROPARAMETER - P. V. Filonov; A. A. Filonova (Научный вестник МГТУ ГА)
An approach to computation of the airport throughput that is based on the quantum model is considered. The description of the quantum system is proposed in terms of macroparameters. The evolution process of quantum system is shown in terms of the markov chain. The transition probabilities between the different states of the system are shown in the analytical form. The dependency between the number of intersection of the SID/STAR - trajectories and airport throughput is considered.